Pengaruh Gaya Kepemimpinan, Kompensasi, dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Aneka Kelola Unggul - Ennor Ennor; Iswati Iswati; Emilia Pranata (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research was conducted to find out about “The Effect of Leadership Style, Compensation, and Work Motivation on Employee Performance” in accordance with the subject matter raised, namely the influence of leadership style, compensation, and work motivation on the performance of employees of PT Aneka Kelola Unggul. The background of this research is that there have been many cases of employee turnover Intention in the company. The purpose of this study was to analyze the effect of leadership, compensation, and work motivation on the performance of employees of PT Aneka Kelola Unggul. The method used in this research is quantitative method. The sample used in this study was the entire number of employees including 50 people using the total sampling method. Technical analysis using multiple linear regression with the help of statistical data processing applications. The conclusion of the results of this study is that leadership style and work motivation significantly and positively affect the performance of employees of PT Aneka Kelola Unggul. While compensation significantly and negatively affects the performance of employees of PT Aneka Kelola Unggul.